2017
DOI: 10.18869/nrip.hdq.2.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Preparedness for Disaster in South Khorasan Province, Ian

Abstract: Background: Nurses, as the largest group in providing relief during disasters with their specialized skills, should be sufficiently prepared to provide the highest level of health care. By compiling predisaster preparedness programs, the provided healthcare would be promoted and number of casualties and incoordination in allocated tasks be reduced. This study was conducted to evaluate nurses' preparedness in response to disasters in South Khorasan Province, Iran. Materials and Methods:In this correlational des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Disaster nursing competencies did not differ according to general characteristics or work‐related characteristics other than in terms of the aforementioned three factors. A previous report on nurses’ clinical experience influencing their clinical competency (Tabiee & Nakhaei 2016) supports our results that disaster nursing competencies were higher among nurses with previous disaster care experience. In addition, considering that nurses with experience in emergency and intensive nursing displayed greater confidence in emergency response than those without such experience (Tzeng et al .…”
Section: Discussionsupporting
confidence: 91%
“…Disaster nursing competencies did not differ according to general characteristics or work‐related characteristics other than in terms of the aforementioned three factors. A previous report on nurses’ clinical experience influencing their clinical competency (Tabiee & Nakhaei 2016) supports our results that disaster nursing competencies were higher among nurses with previous disaster care experience. In addition, considering that nurses with experience in emergency and intensive nursing displayed greater confidence in emergency response than those without such experience (Tzeng et al .…”
Section: Discussionsupporting
confidence: 91%
“…The obtained data suggested that the studied nurses' preparedness for disasters was at a moderate level. This finding is consistent with those of Maeda et al [13] in Japan, Tabiee et al [20] in Iran, Yana et al [21] in China, and Xu et al [22] in Taiwan. However, our finding was inconsistent with those of Matlock [23] in Arkansas, USA, and Whetzel et al [24].…”
Section: Discussionsupporting
confidence: 93%
“…The highest mean score of nurses' disaster readiness was in the aspect of operational competence; therefore, they were appropriately ready to respond to disasters in this area. According to Tabiee et al [20], nurses' disaster readinessin this area was at a moderate level. The low readiness level in this area has also been reported in some other studies [24,25].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, participants were most prepared regarding clinical management and least prepared with regard to emergency response. According to Tabiee and Nakhaei (2016), clinical experiences influenced nurses’ clinical competency. These results were likely due to clinical experience and skills gained during daily practice and clinical management in the hospital.…”
Section: Discussionmentioning
confidence: 99%